Faktor Faktor yang mempengaruhi Nilai Perusahaan : Peran Islamic Social Reporting sebagai Variabel Intervening - Aprilia, Mutik; Rahman, Taufikur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to analyze and prove the influence of Good Corporate Governance and Profitability on Company Value with Islamic Social Reporting as an Intervening variable. This research uses a population of Sharia Commercial Banks in Indonesia registered with the OJK for the 2018-2022 period. The number of samples in this research was 10 companies with 5 research periods obtained using purposive sampling techniques. The analytical methods used are descriptive tests, stationarity tests, regression tests, classical assumption tests, statistical tests, path analysis tests, and Sobel tests. The research results show that the Good Corporate Governance and Profitability variables do not have a significant effect on profitability. Profitability has a positive effect on Islamic Social Reporting. After conducting path analysis and Sobel tests, the ISR variable could not mediate the influence of GCG and Profitability on company value.